Linkage of health care claims data and apps data: The ADVOCATE oral health care dashboard - Frank Gabel; Karen O’hanlon; Pamela Brankin; Robert Bryce; Anna-Lena Trescher; Christian Haux; Helen Whelton; Geert van der Heijden; Stefan Listl (International Journal of Population Data Science, 2017)
ABSTRACT